A Soft-switch Charging Supply based on UC2875 for EMU’ s Storage Battery - LI Hui; TENG Jingfen; XU Li; YU Chong (Kongzhi Yu Xinxi Jishu)
It analyzes the circuit theory of DC-DC converter of battery-charger for CRH1 and CRH5 type EMU(Electric Multiple Unit), and then proposes a new DC-DC converter circuit with ZVZCS to reduce switch-loss. Simulation and test results show that it has stable performances, high efficiency and is an ideal battery charging power supply.